Lifestyle intervention improved nutritional knowledge, dietary composition and health status of midlife Malaysian women - Mohd Yusof, Noor Aini; L.W, Pon; F.B, Ong; N., Adeeb; S.S, Seri; K., Shamsuddin; A.L, Mohammad; N, Hapizah; Awang, Mokhtar; H.W.H, Wan (Persatuan Pemakanan Malaysia, 2006)
Lifestyle has been shown to exert a major impact on the quality of life and health in mid-life women coping with menopausal changes. This study aimed to assess the efficacy of a lifestyle intervention package in improving nutritional knowledge and composition, dietary habits and related health status in mid-life women. Between Nov 1999 to Oct 2001, 360 disease free women, non users of HRT, aged 45 years and above with intact uterus were recruited into the study. The women were randomised into three groups - I (control), II (lifestyle intervention) and III (lifestyle intervention with HRT) respectively. After 12 months, 85.6% completed the study. The lifestyle intervention programme, well accepted by the participants, brought about an improved dietary composition, better eating habits, more exercise participation and increment in knowledge with concomitant improvement of the health status. The benefits observed were significant reduction in energy, fat and carbohydrate intake with increased intake of legumes; milk and cheese/yogurt; and reduction of tea and coffee. Body weight was reduced and more importantly preventing abdominal obesity in the intervention groups with HRT was more effective. Further adaptations of the dietary component with advice on obtaining micronutrients from local produce would contribute towards a more balanced diet in midlife women as dairy products were not popular and these women had low meat intake.